Inhibition of profibrotic microRNA-21 affects platelets and their releasate - Barwari, Temo (JCI Insight, 2018)
Fibrosis is a major contributor to organ disease for which no specific therapy is available. MicroRNA-21 (miR-21) has been implicated in the fibrogenetic response, and inhibitors of miR-21 are currently undergoing clinical trials. Here, we explore how miR-21 inhibition may attenuate fibrosis using a proteomics approach. Transfection of miR-21 mimic or inhibitor in murine cardiac fibroblasts revealed limited effects on extracellular matrix (ECM) protein secretion. Similarly, miR-21–null mouse hearts showed an unaltered ECM composition. Thus, we searched for additional explanations as to how miR-21 might regulate fibrosis. In plasma samples from the community-based Bruneck Study, we found a marked correlation of miR-21 levels with several platelet-derived profibrotic factors, including TGF-β1. Pharmacological miR-21 inhibition with an antagomiR reduced the platelet release of TGF-β1 in mice. Mechanistically, Wiskott-Aldrich syndrome protein, a negative regulator of platelet TGF-β1 secretion, was identified as a direct target of miR-21. miR-21–null mice had lower platelet and leukocyte counts compared with littermate controls but higher megakaryocyte numbers in the bone marrow. Thus, to our knowledge this study reports a previously unrecognized effect of miR-21 inhibition on platelets. The effect of antagomiR-21 treatment on platelet TGF-β1 release, in particular, may contribute to the antifibrotic effects of miR-21 inhibitors.